Kuantifikasi Timbulan Sampah Makanan (Food Waste) di Pasar Tradisional Kota Surabaya Pusat - Dhia Khairullah Risky; Yayok Suryo Purnomo; Aulia Ulfah Farahdiba (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
One of the trading facilities in urban areas is the market. The market is one of the facilities in which there are trading or buying and selling activities between sellers and customers. Expired food or food ingredients, food that has been damaged and food that is not consumed and then discarded by the end consumer can also be referred to as food waste (Food Waste). The existence of waste cannot be avoided in urban areas, unmanaged waste will cause various environmental problems such as floods, disease outbreaks, and others. Therefore, it is necessary to have a treatment for waste generation so that it can avoid environmental problems. The purpose of this study is to determine the generation of food waste originating from market facilities in the city of Surabaya, especially traditional markets, namely the Keputran market and the Genteng market. Data collection on the quantity of FW generated was carried out using the EPA-A Guide to Conducting and Analyzing a Food Waste Assessment method. Market TPS leachate was also tested with BOD, COD, and TSS parameters. The results showed that the total quantification of generation from the North Keputran Traditional Market was 12,236 Kg with an average daily generation of 1,738 Kg/day or 1,748 tons/day, while for the Traditional Market Genteng Market it was 409,196 Kg/day with an average generation of 58,456 kg/day, and leachate testing found information that the leachate produced by the two markets did not meet the regulations or quality standards related to leachate in the Minister of Environment and Forestry Regulation No. P59 of 2016.